Pengaruh Labelisasi Halal Terhadap Loyalitas Konsumen Dalam Mengkonsumsi Makanan Ringan di UNESA Ketintang (studi kasus terhadap anggota organisasi keislaman) - Hasib, Abd.; Anwar, Moch. Khoirul (Jurnal Ekonomika dan Bisnis Islam, 2020)
This research aims to know the effect of the legal label on consumer loyalty in the consuming of a snack on Unesa Ketintang. This research is a study that uses quantitative research that aims to analyze the influence that’s going on between legal label and consumer loyalty in regard to consumption. The data used in this research is data questionnaires and data processing to the spiritual islamic student on Unesa Ketintang. This research uses simple regression analysis using a validation test and reliability test. While for the hypothesis test using t test, f test, and R2 . It may be concluded that in a partial information, the legal label has a significant impact on consumer loyalty. While simultaneously, a legal label with infomation indicators and where legal labelling is significantly seminal